2002
DOI: 10.1177/146442070221600404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size, particle volume fraction and matrix composition on the fatigue crack growth resistance of Al alloy/Al alloy + SiCp bimaterials

Abstract: The fatigue crack growth resistance of Al alloy/Al alloy + SiCp bimaterials for crack growth perpendicular to the interface is affected by thermal residual stresses, elastic mismatch, plastic mismatch and direction of crack approach to the interface. When the crack approaches the interface from the composite side, the crack growth resistance is mainly controlled by the compressive residual stress near to the interface. Conversely, when the crack grows from the aluminium side towards the composite, the crack is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They are likely to affect mechanical and corrosion properties of the materials and therefore influence the in‐service performance of structural components. The effects of residual stresses on fatigue crack propagation have been reported by several authors such as Itoh et al , 1 Bussu and Irving 2 and Milan and Bowen 3,4 . Based on Parker's superposition principle, 5 they concluded that tensile residual stresses increase the crack growth rate due to increasing effective stress ratio ( R ′).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…They are likely to affect mechanical and corrosion properties of the materials and therefore influence the in‐service performance of structural components. The effects of residual stresses on fatigue crack propagation have been reported by several authors such as Itoh et al , 1 Bussu and Irving 2 and Milan and Bowen 3,4 . Based on Parker's superposition principle, 5 they concluded that tensile residual stresses increase the crack growth rate due to increasing effective stress ratio ( R ′).…”
Section: Introductionmentioning
confidence: 90%
“…The effects of residual stresses on fatigue crack propagation have been reported by several authors such as Itoh et al, 1 Bussu and Irving 2 and Milan and Bowen. 3,4 Based on Parker's superposition principle, 5 they concluded that tensile residual stresses increase the crack growth rate due to increasing effective stress ratio (R ).…”
Section: Introductionmentioning
confidence: 99%